Pre-sarcopenia is the prognostic factor of overall survival in early-stage hepatoma patients undergoing radiofrequency ablation. Issue 23 (5th June 2020) - Yeh, Wen-Shuo; Chiang, Pi-Ling; Kee, Kwong-Ming; Chang, Ching-Di; Lu, Sheng-Nan; Chen, Chien-Hung; Wang, Jing-Houng
Abstract : Abstract: Sarcopenia might have impact on the outcome of patients with hepatoma carcinoma (HCC). This study was to determine whether pre-sarcopenia is associated with the outcome of HCC patients undergoing radiofrequency ablation (RFA). Patients with newly diagnosed HCC undergoing RFA were enrolled. We excluded patients without pre-RFA abdominal computed tomography or with incomplete ablation. Psoas muscle area index was calculated at the mid-lumbar 3 level of computed tomography images with the manual trace method. Pre-sarcopenia was defined as psoas muscle area index less than 4.24 and 2.50 cm 2 /m 2 for males and females respectively. The demographics and clinical characteristics were recorded before RFA. All patients were followed regularly until death or end of 2018. A total of 136 patients, including – BCLC stage 0 (n = 44, 32.4%) and – stage A (n = 92, 67.6%), were enrolled (males/females: 78/58, age: 65.4 years) with a mean follow-up period of 3.84 years. There were 75 patients (55.1%) with HCC recurrence and 47 patients (34.6%) with mortality during follow-up. Twenty-two (16.2%) patients were diagnosed with pre-sarcopenia. Multivariate analysis showed pre-sarcopenia (HR: 2.110 (1.092–4.078); P  = .026) was the only factor significantly associated with overall survival (OS); however, there were no factors associated with HCC recurrence. For patients without and with pre-sarcopenia, the 1-, 3-, and 5-year OS rates were 92.0%, 77.6%, 68.9%, and 81.8%, 54.5%, 44.1% respectively ( P  = .007). For early-stage HCC patients undergoing RFA, pre-sarcopenia is the prognostic factor of OS, but not of recurrence, with a worse 5-year OS rate of 44.1%.